2022
DOI: 10.3389/fpubh.2021.783137
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Hospital Violence, Characteristics of Perpetrators, and Prevention and Control Measures: A Case Analysis of 341 Serious Hospital Violence Incidents in China

Abstract: Objective: Hospital violence remains a global public health problem. This study aims to analyze serious hospital violence causes in China and the characteristics of perpetrators. It likewise seeks to understand frontline personnel's needs and put forward targeted suggestions.Methods: Serious hospital violence cases from 2011 to 2020 in the China Judgment Online System (CJOS) were selected for descriptive statistical analysis. A total of 72 doctors, nurses, hospital managers, and security personnel from 20 seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…Similar studies in China have shown comparable findings, with the highest prevalence seen in Guangdong, Jiangsu, and Zhejiang. 6 , 10 The National Bureau of Statistics of China ( http://data.stats.gov.cn/search.htm ) reported that the above provinces had high gross domestic products (GDPs) and large populations. Thus, besides the likely selection bias, we speculate that economically developed provinces attract millions of migrant workers every year—and thus adding to the already overloaded burden of the healthcare staff by residents—has led to a higher frequency of medical WPV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies in China have shown comparable findings, with the highest prevalence seen in Guangdong, Jiangsu, and Zhejiang. 6 , 10 The National Bureau of Statistics of China ( http://data.stats.gov.cn/search.htm ) reported that the above provinces had high gross domestic products (GDPs) and large populations. Thus, besides the likely selection bias, we speculate that economically developed provinces attract millions of migrant workers every year—and thus adding to the already overloaded burden of the healthcare staff by residents—has led to a higher frequency of medical WPV.…”
Section: Discussionmentioning
confidence: 99%
“…WPV rate increased dramatically in 2014 and then dropped after 2016, which might be due to the adoption in China of a series of laws on the punishment of unlawful crimes involving medical services to preserve the regular order of health settings since 2014. 6 For instance, the “Views on Punishing Medical‐related Illegal Crimes and Maintaining Normal Medical Order” jointly promulgated by the Supreme People's Court, the Supreme People's Procuratorate, the Ministry of Public Security, the Ministry of Justice, and the National Health and Family Planning Commission in 2014 states that criminals who had intentionally injured healthcare staff or destroyed public or private property without causing serious consequences should be punished under the “Law on Administrative Punishments for Public Security of the People's Republic of China”. However, those who had intentionally severely injured or killed healthcare staff and other serious consequences should be convicted and punished under the relevant provisions of the “Criminal Law of the People's Republic of China”.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Portugal, where (a) enjoying decent work and a healthy and safe working environment is a fundamental right according to the Constitution, (b) the notifications' trend of situations of violence against health care professionals has been increasing, and (c) violence is considered a crime in the Penal Code, a Action Plan to Prevent Violence in the Health Sector was developed (Direção-Geral da Saúde DGS, 2020). Unfortunately, violence against health care workers is not limited to Portugal: it is a worldwide phenomenon (DGS, 2020;Ma et al, 2022;Vento, Cainelli, & Vallone, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While strong evidence of the efficacy of preventive interventions is still lacking, several measures have been advocated, including quality courses for healthcare professionals (covering communication, identification of early signs that someone may become violent, dangerous situations' management, and self-protection), well-being promotion and psycho social risks (including stress and burnout) prevention, and education of the general population (DGS, 2020; Ma et al, 2022;Vento et al, 2020).…”
Section: Introductionmentioning
confidence: 99%